Dietary patterns of >30, 000 adolescents 9–15 years of age in rural Bangladesh. Issue 1 (12th August 2019) - Thorne‐Lyman, Andrew L.; Shaikh, Saijuddin; Mehra, Sucheta; Wu, Lee S.F.; Ali, Hasmot; Alland, Kelsey; Schultze, Kerry J.; Mitra, Maithilee; Hur, Jinhee; Christian, Parul; Labrique, Alain B.; West, Keith P.
Abstract: Little is known of the usual food intakes of rural adolescents in South Asia. This study describes dietary patterns, based on >91, 000 7‐day food frequencies among 30, 702 girls and boys, aged 9–15 years in rural northwest Bangladesh. Three intake assessments per child, taken across a calendar year, were averaged to represent individual annual intake patterns for 22 food groups. Latent class analysis was used to assign individuals to dietary patterns based on class membership probabilities. The following five dietary patterns (class membership probabilities) were identified: (1) "least diverse" (0.20); (2) "traditional" (0.28); (3) "low vegetable/low fish" (0.23), (4) "moderately high meat" (0.20); and (5) "most diverse" (0.09). The least diverse pattern had the lowest median consumption of most foods and traditional had a relatively higher intake of most vegetables and fish. The most diverse pattern consumed both healthy and processed foods much more often than other patterns. The two most diverse patterns (4 and 5) were associated with higher socioeconomic status, body mass index, height‐for‐age Z‐score, and male gender, and the least diverse pattern showed inverse associations with these characteristics. The most diverse pattern may represent an early wave of the nutrition transition in rural Bangladesh. Abstract : This study describes dietary patterns, based on >91, 000 7‐day food frequencies among 30, 702 girls and boys, aged 9–15 years in rural northwest Bangladesh. Three intake assessments per child, taken across a calendar year, were averaged to represent individual annual intake patterns for 22 food groups. These were then used to generate dietary patterns.